The Conservatives: their Sweetest Victory? - Tim Bale; Paul Webb (Revue Française de Civilisation Britannique)
In the 2015 general election, the Conservative party did not just win an overall parliamentary majority against expectations, but they also increased their national share of the vote and secured additional seats in local government. The article examines the long and short term campaigns and contrasts the 2010 campaign with the one in 2015 to explain their success. It highlights how the Conservatives were able to spin a convincing narrative of Labour economic incompetence and welfare profligacy and capitalise on their opponents’ inner conflicts and voters’ fears of a Labour-SNP coalition. The article argues that their victory is also due to their command of valence issues and their effective targeting of marginal seats.